Measuring self-esteem, work/family enrichment and life satisfaction: an empirical validation - Wan Rashid, Wan Edura; Nordin, Mohamad Sahari; Omar, Azura; Ismail, Izhairi (2011)
This study validates the hypothesized interrelationships among constructs of self-esteem, work/family enrichment and life satisfaction. Using data collected from 680 female nurses employed in public hospitals in Malaysia, this study also examines the likely mediation effect of work/family enrichment on self-esteem-satisfaction relationship. To tests these relationships, the study employs full structural modeling testing using SEM with AMOS 17 data-fitting program. The results indicate that self-esteem is directly influence and has significant effect on life satisfaction. The result provides empirical support for a positive relationship between self-esteem and work/family enrichment.